2015 White Paper on recent issues in bioanalysis: focus on new technologies and biomarkers (Part 3 – LBA, biomarkers and immunogenicity). (December 2015) - Amaravadi, Lakshmi; Song, An; Myler, Heather; Thway, Theingi; Kirshner, Susan; Devanarayan, Viswanath; Ni, Yan G; Garofolo, Fabio; Birnboeck, Herbert; Richards, Susan; Gupta, Shalini; Luo, Linlin; et al.
The 2015 9th Workshop on Recent Issues in Bioanalysis (9th WRIB) took place in Miami, Florida with participation of 600 professionals from pharmaceutical and biopharmaceutical companies, biotechnology companies, contract research organizations and regulatory agencies worldwide. WRIB was once again a 5 day, week-long event – A Full Immersion Bioanalytical Week – specifically designed to facilitate sharing, reviewing, discussing and agreeing on approaches to address the most current issues of interest in bioanalysis. The topics covered included both small and large molecules, and involved LCMS, hybrid LBA/LCMS and LBA approaches, including the focus on biomarkers and immunogenicity. This 2015 White Paper encompasses recommendations emerging from the extensive discussions held during the workshop, and is aimed to provide the bioanalytical community with key information and practical solutions on topics and issues addressed, in an effort to enable advances in scientific excellence, improved quality and better regulatory compliance. Due to its length, the 2015 edition of this comprehensive White Paper has been divided into three parts. Part 3 discusses the recommendations for large molecule bioanalysis using LBA, biomarkers and immunogenicity. Part 1 (small molecule bioanalysis using LCMS) and Part 2 (hybrid LBA/LCMS and regulatory inputs from major global health authorities) have been published in volume 7, issues 22 and 23 of Bioanalysis, respectively.